Effectivity of Large Intestine 4 Point Accupressure on Labour Pain Stage-I Active Phase - Noviyanti; Ratna Dewi; Adri Idiana (HM Publisher, 2021)
Background: Law of the Republic of Indonesia No. 36 of 2009 concerning traditional health services (Yankestrad), namely articles 1, 48, 59, 60 and 61. Acupressure is included in Yankestrad skills that are easy, cheap, simple, effective, and without any side effects. harmful. Acupressure at the Large Intestine 4 Point (LI4) based on the literature is able to reduce labor pain in the first stage of the active phase. Methods: This type of research is quasi-experimental with a pre-test and post-test research design. The samples were divided into two groups, the treatment group and the control group. Results: Based on the results of the research that has been carried out, it can be concluded as follows: Active phase I labour pain before being given Acupressure Therapy for primigravida mothers in PMB Aceh Besar District averaged 7.35. Active phase I labour pain after being given Acupressure Therapy to primigravida mothers in PMB Aceh Besar District decreased by an average of 5.47. Conclusions: There are differences in labour pain in the stage-I of active phase in the Acupressure therapy group with the Routine care group for the stage-I of labour for primigravida mothers in PMB Aceh Besar District.